Early Pottery Technologies among Foragers in Global Perspective Cultural Transformations through Material Practice - D’Ercole, Giulia; Garcea, Elena A. A.; Varadzinová, Lenka; Varadzin, Ladislav (One World Archaeology, 2024)
XXIV, 295 p. 79 illus., 51 illus. in color.